Namiętności i walka z nimi według Marka Eremity - Nieścior, Leon (Collectanea Theologica, 2019)
Writing in his works about passions, Mark the Ascetic had behind him a long-term tradition of ascetic thought. However, an inquisitiveness leads the Master of asceticism to original statements on this subject. In forgetting good thoughts, in recklessness and unawareness (ῥᾳθυμία, λήθη, ἄγνοια) he sees the origin of many passions. The common root of passion is the human tendency to seek pleasure (ἡδυπαθεία). Mark the Ascetic finds in the theologal life, which determined by faith, hope and love, and which is initiated by baptism, the basis of moral innocence of man. In the absence of this life, he sees the cause of the development of evil. He points to concrete measures to fight passions. The forgetting should be contrasted with the memory of good works, the negligence with the sincere readiness to fight, and the unawareness with the enlightened cognition. The author emphasizes the role of meditation, especially of God’s favours and Christ’s abasement, in the fight against faults. As a theologian of the Holy Spirit, he reflects on His role in asceticism.